Projeto de criação e lançamento de uma marca de calçados infantil no mercado brasileiro - Ruppenthal, Lucas Timmen (Universidade do Vale do Rio dos Sinos, 2016)
The objective of the proposed work aims the development of a children's shoe brand creation and launching in the Brazilian market. The relevance of the project is justified because it talks about a different brand profile in the segment of children's shoes, working on fast-fashion’s idea combined with technology resources. This is a trend in which the entire line of this children's shoes collection will be more modern, according to the main fashion trends that follow the lines of the adult shoes segment. The care of the materials quality and the comfort properties of this new collection will remain according to the standard required by the brand target, which largely are the mothers of children - girls from 7 to 10 years, classes A, B and C. The project will have high investment in consumer’s media and a major investment in campaign production. The schedule for the launch in the Brazilian market has been structured in order to launch it at Zero Grau shoes fair in Rio Grande do Sul, on November 21, 2016.
Keywords: Projeto; Lançamento; Calçados infantil; Mercado brasileiro; Project; Launch; Children's shoe; Brazilian market